Characterisation of local damage in pultruded GFRP road bridge decks with random fibre mat misalignments. (January 2022) - Poulton, M.; Sebastian, W.M.
Abstract: The extent to which random, manufacturing-induced fibre mat misalignments compromise the structural integrity of pultruded GFRP road bridge decks is not fully understood. The problem is often critical at the web-flange junctions, which frequently contain the most severe misalignments and are subjected to high moment-shear (M−V) combinations due to local tyre load effects. To that end, in the presently reported experimental study, determinate M−V combinations were applied at the junctions of a pultruded GFRP bridge deck, without artificially restraining (e.g. by clamping, which spuriously strengthens) these junctions. For any given M−V ratio, significant scatter was observed in the damage patterns and loads up to ultimate, owing to random fibre mat misalignments which have been digitally documented in a previous paper. Damage occurred mostly within the junctions, and sometimes in the adjoining flanges. Relative to misalignment-free specimens, the first fracture moments dropped by 19% and 21% for junctions containing flip and wrinkle misalignments respectively. 19% of tests showed higher tangent stiffnesses after damage, probably due to beneficial changes in load-carrying mechanism. A three-pronged approach, based on the load-response, acoustic emission and video data, enables the definition of damage indices, thereby paving the way for integrity assessment of pultruded decks under local tyre load effects.